Conflicts of interest between systemic and corruptive: a conceptual compass for watchdog science journalists - Peters, Cheyenne Moon; Kreutzer, Tobias; Wormer, Holger (Cogitatio, 2026)
Watchdog science journalism is essential to scrutinise the structural and financial conditions of scientific research. As a crucial part of this system, experts play a pivotal role in shaping knowledge, guiding policy, and influencing societal decisions. Their credibility is embedded in a complex web of relationships that brings about different conflicts of interest (COIs). Yet, journalists’ ability to uncover entanglements and ensure accountability is limited by often incomplete disclosure and conceptual vagueness of what exactly constitutes a COI. Using (bio-)medical research as an example, we develop a multidimensional typology of COIs, based on an extensive review of academic literature and disclosure frameworks in science, practice, and policy-making. To our knowledge, this is the most comprehensive mapping of structural, social, and material factors in a single overview to date. While not all these interdependencies are inherently problematic for a functioning research system, they still require journalists to navigate them and carefully evaluate their significance. To facilitate this, the framework also serves as both a matrix and a corrective for potential AI-based systems detecting COIs. Even though transparency and critique are central to watchdog science journalism, journalists should also be careful not to undermine public trust in science generally. Conflicts have to be evaluated carefully but without portraying science funding as inherently corrupt—thus feeding narratives of science-related populism. By foregrounding the systemic nature of COIs, this perspective supports reflection on professional norms, strategies, and principled decision-making in investigative reporting—also regarding journalism’s own entanglements with individual and third-party interests.
Media and communication; 14
Keywords: Conflicts of interest; Expert credibility; Funding transparency; Science journalism; Watchdog journalism; 420; 400; 430; 070; 900; Journalismus; Wissenschaftspublizistik; Interessenkonflikt; Glaubwürdigkeit; Wissenschaft; Forschungsfinanzierung